2015
DOI: 10.1002/chem.201405716
|View full text |Cite
|
Sign up to set email alerts
|

The Gold(I)‐Catalysed Protodecarboxylation Mechanism

Abstract: A mechanistic study of the gold-catalysed protodecarboxylation is described. Each reaction step has been investigated experimentally and computationally. More specifically, the activation parameters for the decarboxylation step have been determined through kinetic studies. Further experimental studies on the hydrolysis of the arylgold intermediate have revealed that the protodeauration can become competitive with the decarboxylation process at high conversions. This switch in rate-limiting step has been shown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…Condensed-phase protodecarboxylation studies have focussed on aromatic carboxylic acids (Shepard et al, 1930;Goossen et al, 2007; and 2-alkynoic acids (Kolarovic&Faberova, 2009;Park&Lee, 2013) using salts of transition metals such as copper (Scheme 4a-c) (Shepard et al, 1930;Goossen et al, 2007;, silver (Scheme 4d) (Goossen, Linder et al, 2009;Cornella et al, 2009;Lu et al, 2009;Xue et al, 2011;Grainger et al, 2014), gold (Scheme 4e) Dupuy&Nolan, 2013;Dupuy et al, 2015), and palladium This article is protected by copyright. All rights reserved.…”
Section: Comparisons With Condensed-phase Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Condensed-phase protodecarboxylation studies have focussed on aromatic carboxylic acids (Shepard et al, 1930;Goossen et al, 2007; and 2-alkynoic acids (Kolarovic&Faberova, 2009;Park&Lee, 2013) using salts of transition metals such as copper (Scheme 4a-c) (Shepard et al, 1930;Goossen et al, 2007;, silver (Scheme 4d) (Goossen, Linder et al, 2009;Cornella et al, 2009;Lu et al, 2009;Xue et al, 2011;Grainger et al, 2014), gold (Scheme 4e) Dupuy&Nolan, 2013;Dupuy et al, 2015), and palladium This article is protected by copyright. All rights reserved.…”
Section: Comparisons With Condensed-phase Systemsmentioning
confidence: 99%
“…Condensed-phase protodecarboxylation studies have focussed on aromatic carboxylic acids (Shepard, Winslow, & Johnson, 1930;Goossen et al, 2007 and 2-alkynoic acids (Kolarovic & Faberova, 2009;Park & Lee, 2013) using salts of transition metals such as copper (Scheme 4a-c) (Shepard, Winslow, & Johnson, 1930;Goossen et al, 2007, silver (Scheme 4d) (Cornella et al, 2009;Goossen, Linder et al, 2009;Lu et al, 2009;Xue, Su, & Lin, 2011;Grainger et al, 2014), gold (Scheme 4e) (Cornella, Rosillo-Lopez, & Larrosa, 2011;Dupuy & Nolan, 2013;Dupuy et al, 2015), and palladium (Scheme 4f) (Dickstein et al, 2007(Dickstein et al, , 2013Nunez Magro, Eastham, & Cole-Hamilton, 2009). Most of these studies have involved homogeneous catalysis, although there has been a report on the development of a heterogeneous supported-silver catalyst (Toy et al, 2014).…”
Section: Comparisons With Condensed-phase Systemsmentioning
confidence: 99%
“…120 Key steps in this reaction have been studied in some depth experimentally and with the aid of DFT calculations. 121 [Au(OH)(NHC)] complexes can be activated using acid, precluding the need for silver additives in synthetic applications such as hydration, hydroamination, hydrophosphoryloxylation, and rearrangement reactions. [122][123][124] When [Au(OH)(NHC)] reacts with half an equivalent of a non-coordinating acid (such as HBF4), dimeric digold hydroxide species [(Au(NHC))2(μ-OH)] + can be isolated (Scheme 37).…”
Section: Goldmentioning
confidence: 99%
“…[14][15][16][17] Due to the high costs involved, only a few studies have been reported for gold-catalyzed protodecarboxylations. [18][19][20] Silver-catalyzed reactions have also emerged in the field of protodecarboxylations and decarboxylative transformations, such as decarboxylative allylations and azidations, and exhibited a highly beneficial reactivity trend, comparable to that of the more costly gold-catalyzed protocols. [21][22][23][24] However, with a few exceptions, 25 such reactions are promoted by soluble silver salts as non-reusable catalytic sources, 26,27 typically in the presence of various ligands, which can be regarded as a considerable drawback from an environmental point of view.…”
Section: Introductionmentioning
confidence: 99%